Assistance for Writing Sermon Scripts Based on Religious Moderation for Islamic Boarding School Students in Metro City - Arifin, Ahmad; Salim, Choirul (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2023)
The background of this service focuses on assistance in writing khutbah manuscripts to santri on religious moderation. This writing class assistance program based on religious moderation aims to improve the understanding of santri literacy in Metro City, which focuses on making Friday sermon scripts. The output of this mentoring program is the publication of a book of khutbah with the theme of religious moderation written by Santri. The approach used in this service is the ABCD (Asset Based Community Development) method with the assets of Islamic boarding school students in Metro. The enthusiasm of the students was extraordinary. The training participants in writing the Friday sermon script were enthusiastic about participating in the training and producing work in a khutbah script printed in the form of a book entitled "Friday Khutbah with the theme of Religious Moderation."